2021
DOI: 10.1590/1809-4392202000391
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of a crop-livestock-forestry system on soil, water and nutrient loss in the Cerrado-Amazon ecotone

Abstract: Soil, water, and nutrient loss by water erosion are among the main factors leading to land degradation, decreasing soil productivity and the provision of ecosystem services. The Cerrado-Amazon ecotone in western Brazil has suffered rapid land-use cover changes with impacts on soil erosion and land degradation. Despite the importance of the region for Brazilian agriculture and environmental conservation, studies on soil, water, and nutrient loss are still scarce. We tested integrated crop-livestock-forestry (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
6
0
8
Order By: Relevance
“…the study from Zolin et al (2021), in which the authors found 16 Mg ha -1 of soil loss when monitoring bare soil during the rainy season. R values are high in this region, similar to the northeast and north, but the lower NEP compared to those regions is due to low values of LS and K, as shown by the high correlation with these factors in Table 3.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…the study from Zolin et al (2021), in which the authors found 16 Mg ha -1 of soil loss when monitoring bare soil during the rainy season. R values are high in this region, similar to the northeast and north, but the lower NEP compared to those regions is due to low values of LS and K, as shown by the high correlation with these factors in Table 3.…”
Section: Resultsmentioning
confidence: 97%
“…It leads in the national production of soybean, maize, cotton, and beef. Concurrently, significant land use changes and high rates of deforestation and soil losses have been observed within the state (Barbosa et al, 2018;Zolin et al, 2021), requiring careful attention. In this context, the objective of this study was to determine the spatial variability of natural erosion potential (NEP) for the state of Mato Grosso, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Other agricultural production systems have gradually become more and more common in the study region and bring with them a strong sustainability bias, which is important for regions with sandy soils. This is the case of integrated production systems (Salton et al, 2014;Zago et al, 2019;Zolin et al, 2021;Bansal et al, 2022), including the integrated crop-livestock (ICL), croplivestock-forest (ICLF), and livestock-forest (ILF) systems. Among other benefits, such as the reconstruction of soil fertility, higher organic matter production, and diversification of plant species, all these systems value the maximization of soil cover by active vegetation and also the higher straw production, characteristics that are very favorable to soil conservation and remediation of the degradation process.…”
Section: Analysis Of Soil Cover In Different Use and Occupation Modelsmentioning
confidence: 99%
“…Como exemplo, grande parte da demanda de energia para as agroindústrias de abate de aves e suínos é suprida pela biomassa de eucalipto na forma de cavacos de madeira (Lenz et al, 2019). A integração bioenergiapecuária consiste numa estratégia de benefícios mútuos para a mitigação do clima e para suprir as demandas de alimentos e fibras da sociedade, usando subprodutos da bioenergia como ração animal para liberar terras para a produção de culturas industriais adicionais (Fiorese, 2021;Souza et al, 2021;Zolin et al, 2021). Mas, a fonte de energia de maior destaque está na utilização do eucalipto para a produção de carvão vegetal utilizado nas indústrias siderúrgicas (Rodrigues et al, 2021).…”
Section: Impactos Benéficos Oriundos Da Produção De Eucalyptusunclassified